2014
DOI: 10.1021/jp502777m
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Calcium Carbonate Nanoparticles in Water and Hydrophobic Solvents

Abstract: The self-assembly of Ca 2+ and CO 2− 3 ions into nanoparticles in water and hydrophobic solvents is investigated using Molecular Dynamics (MD) computer simulation. A new three-stage particle assembly procedure is used which relaxes the structure of the nanoparticle towards a lower energy state. In hydrophobic solvent the bare particle is essentially spherical whereas in water it is ellipsoidally shaped. With surfactant stabilizer the nanoparticles typically exhibit non-spherical cores in model hydrophobic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…This work builds on previous molecular simulations by some of us which concluded that the shape and size of nanoparticles can be controlled by the choice of stabilising surfactant type. 18 The MD simulations carried out here suggest that stearate acting as a co-surfactant in the synthesis of overbased detergents causes a major change in particle shape, and potentially reactivity as an acid neutralisation agent. This co-surfactant induces a normally near-spherical nanoparticle to adopt a rodlike shape, whose dimensions are less dependent on the chemical formula of the surfactant stabiliser than is the case for nanoparticles formed without the stearate additional component.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This work builds on previous molecular simulations by some of us which concluded that the shape and size of nanoparticles can be controlled by the choice of stabilising surfactant type. 18 The MD simulations carried out here suggest that stearate acting as a co-surfactant in the synthesis of overbased detergents causes a major change in particle shape, and potentially reactivity as an acid neutralisation agent. This co-surfactant induces a normally near-spherical nanoparticle to adopt a rodlike shape, whose dimensions are less dependent on the chemical formula of the surfactant stabiliser than is the case for nanoparticles formed without the stearate additional component.…”
Section: Discussionmentioning
confidence: 79%
“…When exposed to a model water droplet, incorporated in the computer model as a new feature, the stearate co-surfactants were found to dissociate from the core, thereby allowing the nanoparticle to absorb deeper into the droplet where the core ions on the surface can interact energetically favourably with the water molecules. Previous simulations 18 only investigated the effects of trace water on the carbonate core, and not with a similarly sized water droplet to the nanoparticle. These simulations are therefore the first of their kind and are a significant step towards the molecular modelling of the overbased detergent function in a realistic chemical environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported recently a more systematic examination of the structural properties of these particles in more realistic model solvents including water. 8 This ambition of modelling more realistically the experimental systems is continued here.…”
Section: Nanoparticle-water Droplet Associationmentioning
confidence: 99%
“…Over time these diffused together and an OD particle self-assembled, which was subsequently equilibrated by gradually reducing the ion charges and 4 then returning them to their original values in two stages, as described in Ref. 8,22 . The thermodynamic integration energy profile proved that in all cases the final state had a lower free energy than the initially formed particle.…”
Section: Simulation Detailsmentioning
confidence: 99%